Electron Paramagnetic Resonance in Lignocellulosic Biomass Pyrolysis Mechanism: Advancements, Applications, and Prospects - Zhongyang Luo; Longyi Liu; Feiting Miao; Wanchen Zhu; Longfei Li; Yuanlin Wang (Energies)
Lignocellulosic biomass can be converted into high-value-added bio-based materials through pyrolysis; however, an unclear pyrolysis mechanism hinders its further application. Electron paramagnetic resonance (EPR) spectroscopy is the most common technology for detecting radicals, which are important intermediates of bond-breaking reactions and coupling reactions during pyrolysis. Hence, this article provides a dedicated review of recent applications, limitations, and prospects of EPR for lignocellulosic biomass pyrolysis. It starts with the advancements of EPR, including EPR spectroscopy principles, radical trapping methods, and spectrum analysis. This review establishes the radical-mediated reaction pathway spanning model compounds to native lignocellulosic biomass, via detecting and identifying the key radicals in the pyrolysis process and pyrolysis products. Furthermore, the effect of biomass pretreatment on the radical behavior during pyrolysis has been emphasized. By providing a comprehensive review of radical evolutionary patterns during biomass pyrolysis using EPR, we conclude with limitations and prospects, which may offer a new perspective on the mechanism of biomass pyrolysis and the optimization of pyrolysis conditions.